The Influence Of Aging Time To Mechanical Properties On Aluminum Silicon - Connie, Bato (UTeM, 2010)
Heat treatment is a process to alter the structure and properties of the materials used. Heating to a higher temperature, go through aging and tempering of the aluminum silicon alloy increases the strength at the expense of ductility. At the mean time, the alloys become though. Addition of the silicon composition in aluminum silicon alloy affects the structure and properties of this alloy. Tensile strength and hardness tests were performed in order to analyze the properties. The results showed that at a higher silicon content, the alloy becomes less ductile and harder because of the presence of harder and more brittle silicon particles.